Kewenangan Panitia Urusan Piutang Negara Ditinjau Dari Teori Sistem Hukum - Muhamad Arifianto (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
The position of the Committee for State Receivables (PUPN), from a constitutional point of view, should be able to become a strong and professional representative interdepartmental institution in line with the goals and expectations of its establishment in accordance with laws and regulations to support the wheels of the economy and benefit the country's finances at a macro level. The problem in this study is regarding how PUPN's authority is viewed from the point of view of the legal system theory. The method used in this research is descriptive research method with a normative juridical approach. Law Number 49 Prp of 1960 concerning the Committee for State Receivable Affairs, is the forerunner of the paradigm for settlement of State Receivables by incorporating elements of managing and collecting state debts with very effective and strong authority from a legal standpoint. In addition, the institutional form that is interdepartmental gives a special image and the presence of law enforcement officials in it can have a significant psychological effect on the debt guarantor. Not to mention that the PUPN itself is equipped with parate execution powers which are the same as the court's execution powers.